What is the missing exponents in the following equation. h^450/h? = h^215

11 answers

To solve for the missing exponents in the equation \( \frac{h^{450}}{h?} = h^{215} \), we can use the properties of exponents.

When dividing two powers with the same base, you subtract the exponents:

\[ \frac{h^{450}}{h?} = h^{450 - ?} \]

Setting this equal to \( h^{215} \) gives us the equation:

\[ h^{450 - ?} = h^{215} \]

Since the bases are the same, we can equate the exponents:

\[ 450 - ? = 215 \]

Now, we solve for the missing exponent \( ? \):

\[ ? = 450 - 215 = 235 \]

Thus, the missing exponent is \( 235 \). Therefore, the equation is:

\[ h^{450}/h^{235} = h^{215} \]

R u sure?

Let's double-check the calculation step by step to ensure it's correct.

Given the equation:

\[ \frac{h^{450}}{h?} = h^{215} \]

Using the properties of exponents, we know:

\[ \frac{h^{450}}{h?} = h^{450 - ?} \]

Setting this equal to \( h^{215} \) gives us:

\[ h^{450 - ?} = h^{215} \]

Since the bases are the same, we can equate the exponents:

\[ 450 - ? = 215 \]

To find \( ? \), we rearrange the equation:

\[ ? = 450 - 215 \]

Calculating that gives:

\[ ? = 235 \]

So the missing exponent is indeed \( 235 \). The step-by-step verification confirms that the original conclusion is accurate.

Simplify 12^87 divide by 12^25

To simplify \( \frac{12^{87}}{12^{25}} \), you can use the properties of exponents. Specifically, when you divide two powers with the same base, you subtract the exponents:

\[ \frac{a^m}{a^n} = a^{m-n} \]

Applying this to our expression:

\[ \frac{12^{87}}{12^{25}} = 12^{87 - 25} = 12^{62} \]

Therefore, the simplified form of \( \frac{12^{87}}{12^{25}} \) is \( 12^{62} \).

Which one?

The simplified result of \( \frac{12^{87}}{12^{25}} \) is:

\[ 12^{62} \]

So the final answer is \( 12^{62} \).

What is the value of 6.9-2^0

To solve the expression \( 6.9 - 2^0 \), we first need to evaluate \( 2^0 \).

According to the properties of exponents, any non-zero number raised to the power of 0 is equal to 1. Thus:

\[ 2^0 = 1 \]

Now, we substitute \( 1 \) back into the expression:

\[ 6.9 - 2^0 = 6.9 - 1 \]

Calculating this gives:

\[ 6.9 - 1 = 5.9 \]

Therefore, the value of \( 6.9 - 2^0 \) is \( 5.9 \).

Apply the zero power rule to create an equivalent expression to 9* (-33)^0 + 3/2 (8 - 27^0)

9* (-33)^0 + 3/2 (8 - 27^0) = blank * blank + 3/2 ( blank - blank)

The zero power rule states that any non-zero number raised to the power of zero equals 1. Thus, we can simplify the expression \(9 \cdot (-33)^0 + \frac{3}{2}(8 - 27^0)\) step by step.

  1. Apply the zero power rule:

    • \((-33)^0 = 1\)
    • \(27^0 = 1\)
  2. Substituting these values back into the expression:

    • \(9 \cdot (-33)^0 = 9 \cdot 1 = 9\)
    • \(27^0 = 1\) thus the expression becomes: \[ 9 + \frac{3}{2}(8 - 1) \]
  3. Now simplify \(8 - 1\): \[ 8 - 1 = 7 \]

  4. Substituting this back into the expression: \[ 9 + \frac{3}{2} \cdot 7 \]

  5. Now calculate \(\frac{3}{2} \cdot 7\): \[ \frac{3 \cdot 7}{2} = \frac{21}{2} \]

Thus, the original expression simplifies to:

\[ 9 + \frac{21}{2} \]

Now, to match your requested format:

\[ 9 \cdot (-33)^0 + \frac{3}{2} \left( 8 - 27^0 \right) = 9 \cdot 1 + \frac{3}{2}(7) \]

So filling in the blanks gives:

\[ 9 \cdot 1 + \frac{3}{2}(7) \]

Final answer:

\[ 9 \cdot 1 + \frac{3}{2}(7) \]

Similar Questions
    1. answers icon 1 answer
  1. Quotient Rule of ExponentsWhat is the missing exponent in the following equation? 3 E?/e65 = e/38
    1. answers icon 1 answer
  2. What is the missing exponent in the following equation?S⁵⁰⁰/S^? = S¹⁷⁵ Note: only type the exponents in the box, do
    1. answers icon 1 answer
  3. Use the Product Rule of Exponents to simplify 5^10 x 5^55^50 25^15 25^50 5^15 Find the numerical equivalent of
    1. answers icon 5 answers
more similar questions